Christ Church on Salem Street, ca. 1890 - Detroit Publishing Company (Tufts Archival Research Center, 2005)
Street-level view southeast of Christ Church, located on Salem Street at the southeast end of Hull Street. The facade of the church faces northwest. Buildings line both the northeast and southwest sides of Hull Street. An awning adorns the facade of a building located on the northwest corner of Salem and Hull Streets. A group of men and a street light are also visible on the same corner. Designed by William Price, 1723; also known as the Old North Church 9 x 6 15/16 overall Photographs